Anti-bribery and Corruption Policies in International Sports Governing Bodies - Christina Philippou; Tony Hines (Frontiers Media S.A., 2021)
International Sports Governing Bodies ("ISGBs") are diverse in their aims but share a need to maintain a reputation of accountability in the eyes of their stakeholders. While some literature analyses the general governance concerns faced by these organizations, there is limited focus on anti-bribery and corruption ("ABC") within this sphere. This paper's research aim is an exploratory evaluation of the ABC best practice policies that exist within ISGBs, asking how they can be assessed and what best practice policies currently exist within this framework. This paper undertakes a critical review of the diverse ABC governance policies in the largest ISGBs through content analysis on governance documents publically available on the sample ISGB websites. This review was undertaken twice on the same ISGBs, in 2017 and 2020, and the changes reviewed. The research highlights best practice policies for recommendation to all ISGBs, and illuminates the absence of adequate policies with regards to the risk of bribery in ISGBs. The findings show there was no area within the framework that ISGBs performed well at as a collective, and there was no single ISGB whose anti-bribery policies were strong in all areas. However, the comparison between 2017 and 2020 shows an improvement in ABC policies in some ISGBs over the timeframe analyzed. The implications are a need for sharing best practice in this area of governance, and providing global guidance on ABC policies for ISGBs to ensure integrity in the sector.